Fast pitch - Stone, Nic (Crown Books for Young Readers, 2021)
"Shenice Lockwood dreams of leading the Fulton Firebirds to the U12 softball regional championship. But Shenice's focus gets shaken when her great-uncle Jack reveals that a career-ending-and family-name-ruining-crime may have been a setup. It's up to Shenice to discover the truth about her family's past-and fast-before secrets take the Firebirds out of the game forever"--